Enhancing stunting prevention: Health promotion at Bandarharjo Health Center - Nurlian Ramadhanty; Syamsulhuda Budi Musthofa; Ani Margawati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting is a serious public health problem that affects child growth in many countries. Health promotion programs are key strategies for raising awareness and encouraging behavioral changes to address stunting. This study aimed to analyze the implementation of health promotion programs to prevent stunting. The research design was qualitative with a case study method, and information was collected through in-depth interviews with 13 informants at Bandarharjo Community Health Center (PHC) from October to December 2023 and then analyzed through a series of stages: collection, reduction, presentation, and conclusion drawing. Results: In terms of human resources, Integrated Service Post (ISP) cadres have not received equal training in the use of anthropometric tools. Educational media such as posters and flip sheets are not provided to cadres for use. The facilities and infrastructure at the ISP are inadequate for toddlers. After the Covid-19 pandemic, the implementation of health promotion was strengthened and improved. Increased training for program holders and cadres to improve competence. Educational media have not been fully optimized to convey information about stunting to program targets. Some areas do not have ISP buildings. After the pandemic, the focus of the program implementation was more oriented towards health promotion. Increased supervision is required in health promotion programmes to prevent stunting.